UTILIZATION OF PHET SIMULATIONS AS EFFORT TO SOLVE LEARNING DISABILITY OF DEAF STUDENTS IN DYNAMIC ELECTRICITY MATERIALS - Alffina Nurhasanah (Universitas Muhammadiyah Semarang, 2018)
Based on section 31 part 1 in UUD 1945 states education is right of everyone in Indonesia. Belongs to student with special needs is like deaf students. That’s why has been done a research to try phet simulations as a visual media to the deaf students. This aim of this research is to describe the result of phet simulations visual media using to solve deaf student problem in studying at electricity matter and the students’ response. This research use qualitative descriptive method by using data analyzing technique from Miles and Hiberman (in Pasarela, 2012 : 44). Data will be collected, then reduction step, then be presented, and for the last will be verified (be concluded).The result is the main studying difficulty of students is poor of words so that the students can’t understand the words in sentences as soon as possible. Moreover, the schedule of science is only once in a week and student prefers to use sign language than oral language, that makes student poorer in words and sentences. That’s why phet simulations media is given as learning media in class because this media consist of lots picture and has interested slide and the students give positive response. It’s supported by evaluation result that shows good changing so that means this media is good and suitable as learning media to deaf student. From data analysis of research, be got conclusion that phet simulations visual media using can be used as effort to solve studyingdifficulty of deaf student in dynamic electricity matter and the students give positive response too. Keywords: deaf student, studying difficulty, phet simulations, dynamic electricity